Waqf in Non-Muslim Countries: A Case Study of Singapore - Rusydiana, Aam Slamet; Ali, Mohammad Mahbubi (International Journal of Waqf, 2024)
Waqf is an Islamic concept that refers to a charitable endowment or trust. It involves dedicating a specific asset, such as property, land, or money, for the benefit of the community or a specific purpose, in accordance with Islamic law. One of the important aspect in the success of waqf is the management and optimization concept. This research will try to elaborate further on the development of waqf in the non-Muslim country of Singapore. This paper also tries to look at the revitalization of existing waqf land in Singapore, given its very limited area. The result show that, although it is Muslim-minority country, Singapore is able to professionally manage its waqf assets and properties productively. Through MUIS, waqf is managed optimally. The impressive performance of Warees, an important philanthropic institution in Singapore, cannot be separated from its professionalism, innovation in financing, initiation of cash waqf and the release of fatwa on istibdal waqf.